Educação em saúde e microbiologia: concepções e estratégias didáticas de futuros professores de Biologia no âmbito do Programa Residência Pedagógica - Pires, Fabiele Rosa (2024)
This dissertation was developed in the thematic line Scientific Education: teaching and learning processes at school, university and research laboratory and addresses aspects related to Health Education (HE), which is configured as a broad area, from which several aspects emerge. that trigger a relationship with everyday school life. The area of Microbiology has content that has a considerable relationship with SE, being responsible for the development of notions about microorganisms, which have a great relationship with human health. Therefore, we consider this approach to be of fundamental importance in everyday school life. However, with the implementation of the National Common Curricular Base (BNCC) it is noted that the theme of higher education is not covered in a significant way. Thus, it highlights the importance of teachers looking beyond this document, inserting this fundamental knowledge into the contents developed in the classroom. As a result, we believe that the relationship between Microbiology and health should be present in discussions from the initial training of teachers, so that they can be addressed in Basic Education classrooms. Based on this, the Pedagogical Residency Program (PRP) offers contributions to the training of its participants, since among its demands there is an adaptation of residents in the field school space, preparation of lesson plans and development of educational practices, actions that are fundamental to the training process. Thus, this dissertation aims to understand the didactic possibilities, about the relationship between microorganisms and health, that emerge from plans prepared by future teachers for Biology Teaching in High School. The methodological assumptions are characterized in qualitative research in relation to the approach to the problem, and explanatory according to its objectives. The first movement of the study resided in a bibliographical research, which analyzed works that related Microorganisms with Health. Three searches were carried out, namely: 1) in the Minutes of the National Meetings of Research in Science Education (ENPECs); 2) in the Magazine Ensino, Saúde e Ambiente; 3) in the Brazilian Digital Library of Theses and Dissertations (BDTD). The analysis of the works arising from the searches, enabled us, through Content Analysis, to the emergence of three categories: (A) Approach to the topic of microorganisms in textbooks and Teacher Training - five (5) works; (B) Perceptions of topics relating to microorganisms and health - seven (7) works; (C) Didactic strategies for working on topics related to microorganisms and health - thirty-one (31) works. After completing the bibliographical study, a field research was carried out, in which, for data production, the Cooperative Planning technique was used, which is structured as a tool for research into didactic situations, teaching methodologies, as well as investigation of teachers' conceptions. The development of the technique occurred through the implementation of a teacher training course, in the format of remote meetings (via Google Meet platform) with the offering of synchronous and asynchronous activities distributed across the five (5) stages of Cooperative Planning: (1) Initial discussions; (2) Questions; (3) Organization of the action; (4) Didactic action; (5) Didactic assessment and self-assessment. The material produced using the Cooperative Planning method was analyzed using the Content Analysis Technique, which enabled the emergence of the following categories: (A) Residents' initial perceptions and (B) Planning and approaches regarding the relationship between microorganisms and health. Thus, in category (A) residents' initial perceptions regarding the approach to microorganisms and health were grouped, as well as the preparation of plans. In this category, residents highlighted the lack of training on health issues and the strategies they thought of to address the issue in planning. In category (B), the analyzes of the plans were focused, emerging ten (10) plans, which contained diverse teaching strategies. We observed that each plan demonstrated a diverse sequence of strategies to address the proposed theme. Finally, we indicate the power of programs such as PRP for initial teacher training. Furthermore, we highlight the need for initial training on the approach to the relationship between Microorganisms and Health, as residents lack knowledge on how to approach health-related topics, as well as the relevance of carrying out the approach in the classroom and the interest and curiosity of students about topics regarding Health Education and Microbiology in the Biological Sciences Course.